Hydropower Infrastructure and People Empowerment (Case in Pesangkalan and Gumelem Kulon Villages, Banjarnegara) - , Mia Zuhara Primasari ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The objectives of this research are to study utilization of hydropower infrastructure related to community development, to describe impact of hydropower infrastructure that affects people empowerment and to propose strategies the improvement of local institution of society. The research takes place in two villages, those are Pesangkalan and Gumelem Kulon, Banjarnegara. This research represents a case study using qualitative method. Data are gathered through interview, documentation, observation and focus on group discussion. Afterwards, the data go through editing, coding and triangulation. Finally, they are displayed in a way of description and tendency interpreted in such a way so that they can be understood properly. Both Pesangkalan and Gumelem Kulon have different utilization of hydropower infrastructure. Pesangkalan has formal local institute on while Gumelem Kulon has nonformal local institution. The first system produces inefficient, effective and equal delivery mechanism of infrastructure. The latter establishes cohesive institutional and bottom-up approach. This second system produces inefficient, effective and equitable delivery mechanism of infrastructure. The impact of hydropower infrastructure utilization does not affect people empowerment in Pesangkalan. The domination of apparatus causes the collective capabilities of society do not develop through local organization (Organisasi Masyarakat Setempat/ OMS). Therefore, the society has no capacity to design the programs that produce certain incomes from hydropower management. The apparatus dominates the benefit of Organisasi Masyarakat Setempat/ OMS. Nevertheless, it is different from Gumelem Kulon in which the hydropower infrastructure utilization affects people empowerment there. The collective capabilities of society develop through non-formal community, so that they have capacity to design the programs that produce certain incomes. Although there is no formal institution, but management of hydropower infrastructure is running well. Based on the findings above, there are three recommendations, first is to change the system of utilization, i.e. from the apparatus-controlled one toward the societycontrolled one to revitalize spirit of people empowerment in Pesangkalan. Second is to reform the formal local institution in managing hydropower infrastructure more professional in Gumelem Kulon. Third, Government of Banjarnegara should create energy (hydropower infrastructure utilization) as the priority of development program.